Time-of-day dependent promotion of keratinocyte differentiation by Cinnamomum cassia bark extract through the p38 MAPK Pathway - Miji Yeom; Kyungeun Jeon; De-Hun Ryu; Deokhoon Park; Eunsun Jung (PLoS ONE, 2025)
The skin serves as an essential barrier against pathogens and external insults, preventing moisture loss. Chronic skin conditions such as atopic dermatitis stem from impairments in skin barrier function. Circadian rhythms affect skin blood flow and barrier characteristics, which are significant for understanding atopic dermatitis. Cinnamomum cassia bark, commonly known as cinnamon, is extensively utilized in both modern and Traditional Chinese Medicine for its therapeutic properties in managing chronic diseases. This study aimed to investigate the potential use of Cinnamomum cassia bark in enhancing skin barrier function. We examined the impact of Cinnamomum cassia bark extract (CCBE) on circadian clock-mediated enhancement of the skin barrier. CCBE enhanced the expression of keratinocyte differentiation markers, including keratin 10, filaggrin, caspase 14, and calpain-1. CCBE also increased the production of hyaluronic acid protein. Additionally, CCBE improved the circadian rhythm of period circadian regulator 2 (PER2). Notably, CCBE upregulated the expression of keratinocyte differentiation markers and PER2 specifically during the morning hours. Furthermore, we discovered that siRNA-mediated PER2 knockdown diminished the increase in keratinocyte differentiation markers induced by CCBE. These findings demonstrate that CCBE can regulate the differentiation of keratinocytes in a time-of-day-dependent manner via the circadian clock. CCBE augmented phosphorylation of p38 and JNK, while the CCBE-induced enhancement in FLG expression and PER2 circadian rhythm was reduced by p38 MAPK inhibitors. These results suggest that CCBE can strengthen the skin barrier diurnally via the p38 MAPK pathway, representing a novel and more effective method for enhancing skin barrier function that accommodates daily variations in skin barrier properties.